Tambo Viejo: un asentamiento fortificado en el valle de Acari, Peru - Valdez, Lidio M. (My University, 2013)
The emergence of violent conflict and of fortified settlements is a subject little studied within Peruvian archaeology. However, I consider it vital to investigate and determine the time and the reasons under which fortified settlements were first established. The central aim of this paper is to discuss when and why fortified settlements emerged first in the Acari Valley and, by extension, in the south coast of Peru. Available archaeological evidence indicates that during the Early Intermediate Period, Tambo Viejo was a fortified settlement protected by several massive walls. Other neighbouring sites in Acari were also fortified. Furthermore, in Acari there is conclusive evidence for violence in the form of decapitated individuals. In contrast to evidence coming from Acari, not a single Early Intermediate Period settlement from other valleys of the Peruvian south coast can be securely identified as fortifications, thus making the Acari sites the earliest fortified settlements of the entire Peruvian south coast.
Tambo Viejo: a fortified settlement in the Acari Valley, Peru
Keywords: fortification; violent conflict; Peruvian south coast; Acari; Early Intermediate Period